Implementasi Konseling Multikultural dalam Masyarakat Plural di Toraja - Dickyryan Gangga; Resti Pantinggi; Selvi Datu Arruan; Wulan Dini Manati; Ronaldo Stefanus (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Toraja is a region in Indonesia widely recognized for its strong cultural traditions, diverse beliefs, and social stratification that continues to shape daily interactions and social dynamics. This cultural pluralism often creates challenges in identity formation, communication, and adaptation among community members. Multicultural counseling is an appropriate approach to meet the needs of Toraja society since it acknowledges the cultural and religious background of clients throughout the counseling process. This study adopts a qualitative literature review method to analyze the implementation of multicultural counseling, including challenges and strategies for its effective application in Toraja. The results indicate that multicultural counseling becomes successful when counselors possess multicultural competency, collaborate with traditional and religious leaders, and integrate local wisdom such as sirik na pesik (respect for dignity), tolerance, and communal support. Thus, multicultural counseling plays a crucial role in promoting harmony and improving psychological well-being within Toraja’s plural society.